2007
DOI: 10.1007/s10762-007-9291-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance Test of CW 300 GHz Gyrotron FU CW I

Abstract: A 300 GHz CW gyrotron FU CW I has been developed and installed in the Research Center for Development of Far-Infrared Region, University of Fukui as a power source of a high frequency material processing system. Its performance was tested and the maximum power of 1.75 kW / CW has been attained at the beam voltage of 15 kVand the beam current of 1A. The maximum window power efficiency of 15.5% has been obtained at the cathode voltage slightly lower than 15 kV. This gyrotron is designed to deliver a Gaussian bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This, in principle, makes possible the occurrence of diverse multimoding phenomena [11][12][13] such as nonlinear excitation of parasitic modes [13], mode competition and cooperation [14][15][16], mode suppression, mode jumping [17] (also known as mode shift [18]), mode locking, simultaneous oscillation of several modes [19,20] etc. The experimental investigation of the oscillation characteristics of FU CW I and especially the study of its radiation patterns [7,8] have indicated that this tube exhibits a complex behavior which could be explained namely by mode interaction. In order to check some of the working hypothesis and get better physical insight in the underlying processes a series of numerical experiments (presented in the preceding section) have been carried out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This, in principle, makes possible the occurrence of diverse multimoding phenomena [11][12][13] such as nonlinear excitation of parasitic modes [13], mode competition and cooperation [14][15][16], mode suppression, mode jumping [17] (also known as mode shift [18]), mode locking, simultaneous oscillation of several modes [19,20] etc. The experimental investigation of the oscillation characteristics of FU CW I and especially the study of its radiation patterns [7,8] have indicated that this tube exhibits a complex behavior which could be explained namely by mode interaction. In order to check some of the working hypothesis and get better physical insight in the underlying processes a series of numerical experiments (presented in the preceding section) have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…It has already demonstrated high performance and output parameters corresponding to the design target values. In order to study in detail its operational characteristics a set of experiments have been carried out [6,7]. In these experiments several interesting phenomena have been observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The cavity mode is TE 22,8 at the fundamental operation. [20,21] The second gyrotron, Gyrotron FU CW II [14][15][16] was constructed and the operation test has been carried out. The principal designed cavity mode is TE 2,6 at the frequency of 394.6 GHz.…”
Section: Introductionmentioning
confidence: 99%